Depression Levels of University Students and Changes in their Nutritional Status in the COVID-19 Pandemic Quarantine Period: A study in Turkey - Baygut, Hatice (Progress in Nutrition, 2022)
Abstract:Objective: The objective of this study was to examine the depression levels and nutritional changes of university students during the COVID-19 pandemic quarantine process.Method: A cross-sectional study was conducted in 4528 university students, aged between 18-42 years, living in Turkey. A questionnaire form questioning demographic characteristics, anthropometric measurements, dietary changes and BECK Depression Inventory was sent to the university students via the online system (via google form). Analysis results are presented as mean ± standard deviation and median (minimum – maximum) for quantitative data, and categorical data are presented as frequency (percentage).Results: There was a statistically significant relationship between gender and the BDI score (p